RESPON VARIETAS JAGUNG TERHADAP PEMBERIAN AMELIORAN KAPUR DI LAHAN SULFAT MASAM - SARI, FITRIA; SUSANA, RINI; MAULIDI, MAULIDI (Jurnal Sains Mahasiswa Pertanian, 2017)
RESPONSE OF MAIZE VARIETIES TO LIMING ON FLUVAQUENTS Â  Fitria sari 1), Rini Susana 2),Maulidi 2),Basuni 2) 1)University student and 2)Lecturer Study Program of Agrotecnology Facultyof Agriculture Tanjungpura University ABSTRACT This study aims to investigate the response of corn to plant varieties of lime. Research conducted at the Desa Parit Canggek snapper Kubu Raya regency in West Kalimantan. The method used in this research is of split plot design using randomized complete block. The treatment consists of the main plots (lime) with three levels (k1 = 0,8 kg /subplot is equivalent to 1 ton/ha, k2 = 1,6 kg /subplot equivalent of 2 ton/ha and k3 = 2,4 kg/subplot equivalent to 3 ton/ha) and subplots (varieties) with 2 levels (v1 = Sukmaraga and v2 = Bima 7), thus there are six treatment combinations, each treatment replicated 3 times. The variables observed in this study were plant height, dry weight, cob length, cob diameter, cob weight, weight of 1000 seeds and dry seed weight/plot. The results showed that the lime and the interaction of lime and varieties maize was not significant effect to all the variables of observation, whereas varieties have significant effect on plant height, dry weight of the upper part of plant, cob diameter, weight of 1000 seeds but there is no significant effect noticeable to the length of the cob, cob weight and dry seed weight/ plot. Sukmaraga significantly different with the Bima 7 on plant height, dry weight, cob diameter and weight of 1000 seeds. Keywords: Fluvaquents, Lime, Maize